Metacognition, Study Approaches and Reading Attitude: Towards Improving Reading Efficiency in English - Abu Bakar, Mohamed (2002)
The study investigated aspects of metacognition, study approaches and reading attitude of university students to enhance reading efficiency in English. A total of 503 students enrolled in the proficiency courses at UPM participated in the study. Three hundred and eighty-five students participated in the questionnaire survey and 118 students were involved in the needs analysis. From this population of 503 students, 40 students took part in the quasi-experimental study and out of this sample, ten students were randomly selected for the unstructured interview. It is also important to note that ten lecturers took part in the students'needs analysis. The results of the needs analysis have shown that factors like metacognition, study approaches and reading attitude are important for reading efficiency. It is noted from the questionnaire survey (metacognition and study approaches) that variables like programme of study, home background, gender and race were not related to reading efficiency among students. The main factor that revealed a significant difference in reading efficiency was students' SPM English grades. Students with distinctions and credits in English at SPM appeared to have a high level of metacognitive awareness, effective study approaches and a positive reading attitude in English. Besides, the questionnaire survey has shown a strong relationship between study approaches and reading attitude. In like manner, metacognition is guided by students' positive reading attitude. The results of the quasi-experimental study have shown that average readers at the university level can increase their reading rate by about 27%, and their comprehension score by 22%. A pre and post-test administered for both treatment and control groups have shown a convincing improvement for treatment group students. In fact, all participants of the treatment group gained in their overall score after the eight weeks' (16 hours) of training on reading efficiency. The interview results revealed that both treatment and control group students faced problems in reading. However, most of the treatment group students have learnt to overcome some of these problems. On the other hand, control group students have said that they did not know how to solve their reading problems. Both treatment and control group students have shown elements of metacognitive awareness. However, what were lacking for the control group students were strategies, both reading and metacognitive strategies. The study has proposed a reading efficiency model to enhance speed and comprehension in reading. The reading efficiency model proposed in this study with its three major components that is metacognition, study approaches and reading attitude is felt practical and applicable to students. And finally, the findings of this study have established the need for training in reading efficiency for students taking the English proficiency courses at UPM and similarly placed students elsewhere in the country.